2017
DOI: 10.4034/pboci.2017.171.40
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, Components of Empathy and Curricular Evaluation of the Faculty of Dentistry, Evangelical University of El Salvador

Abstract: Objective: To estimate empathy levels in general and empathic growth potential in dental students. Material and Methods: This is an exploratory, transversal study. The study population is made up of students from the first to fifth academic year of the career of dentistry of the Evangelical University of El Salvador (El Salvador) (148/240, 61.67% of the population studied). The participants were given the Jefferson Empathy Medical Scale, the Spanish version for medical students, validated in Chile and Mexico, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(29 reference statements)
0
6
0
1
Order By: Relevance
“…In the case of undergraduate education, interventions should be carefully planned, as deeply as possible, sustained over a long time and should include complex actions provided by specialised interdisciplinary teams. 40,44,49 In relation to the differences between the different dental specialties, already discussed above, the authors of the present work Therefore, the practical importance of this study is to infer that empathic training of graduate students in dental specialties does not depend on the training they receive at this level, but on the training they have received ("inherited") in undergraduate education.…”
Section: It Is An Important Finding That the Dimensions CC And Puttingmentioning
confidence: 67%
See 1 more Smart Citation
“…In the case of undergraduate education, interventions should be carefully planned, as deeply as possible, sustained over a long time and should include complex actions provided by specialised interdisciplinary teams. 40,44,49 In relation to the differences between the different dental specialties, already discussed above, the authors of the present work Therefore, the practical importance of this study is to infer that empathic training of graduate students in dental specialties does not depend on the training they receive at this level, but on the training they have received ("inherited") in undergraduate education.…”
Section: It Is An Important Finding That the Dimensions CC And Puttingmentioning
confidence: 67%
“…However, it has been observed that such trend is not representative of the empirical data obtained by some authors which reflect conflicting results. 22,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] On the other hand, gender empathy has been studied in homozygotic and dizygotic twins 46 and possible gender-specific innate and environmental influences on empathy and its cognitive and emotional components were found. In relation to the differences found in the present work (higher in women) in the values of Empathy and PA, and, in particular with the PA dimension.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, a single “significant” change could be interpreted as a success, even though that change may not be that successful. Given that the concept of empathy is complex, the construction of cutoff points becomes important as a quantitative structure that makes it possible to quantify the magnitude of change in these levels and, furthermore, to have certain points of reference to credit the real meaning and true impact of an intervention to raise empathy levels 3,6,8,10,35–37 …”
Section: Discussionmentioning
confidence: 99%
“…In Latin America, empathy has been examined in students of different careers. One of the most commonly used instruments is the Jefferson Scale of Physician Empathy (version S)(JSPE‐S) for medical students, adapted for other health careers, and in this case dental students 3,4–11 . Its psychometric characteristics have been exhaustively studied and are comprised of 3 components or dimensions: perspective adoption (PA), compassionate care (CC), and “walking in patient's shoes”(WIPS) 9,12–19 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this fact, when reviewing the curricular contents for the cohorts of the years compared, it is evident that curricular contents could be considered as modifiers of the empathy levels in students [27,28]. To the present study our could identify that the curricular contents and professors were not necessarily the same for both cohorts, which indicates that the developed theme by professors by virtue of their methodological strategies, the way students are evaluated and finally the learning atmosphere can generate variations in students' perception of the educational environment, which has a direct relation and relevance to their well-being and fulfillment of the academic achievements [29], about the latter, within the academic achievements could emphasize the development of relevant and required humanistic and social skills for health care.…”
Section: Discussionmentioning
confidence: 99%